PPM PENINGKATAN KAPASITAS DAN KUALITAS USAHA HAPPY TEA DALAM MENINGKATKAN DAYA SAING PRODUK LOKAL - Nur Holifah; Novita Maulida Ikmal; Indriastuti Indriastuti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The Community Service Program (PPM) implemented by the Happy Tea business aims to increase the capacity, quality, and competitiveness of local products amidst the dynamics of the competitive beverage market. The Happy Tea business was selected as a partner because it has the potential to develop local tea-based products that can be developed through innovation, modern marketing, and more professional business management. This community service activity is carried out through three main interventions. First, providing production facilities in the form of freezer box machines and stainless steel pans as supporting facilities for developing a new menu, namely spiced tea, which is expected to attract consumer interest by offering a distinctive taste and health benefits. Second, holding online media-based marketing training focused on the use of digital platforms to expand market reach, improve branding, and build more intensive interactions with consumers. Third, financial management training was provided to strengthen business governance, including transaction recording, capital management, and systematic financial planning. The program's implementation has shown positive results, including increased production capacity, increased product variety, improved skills among entrepreneurs in utilizing digital technology for promotion, and improved financial management skills. Thus, this Community Service Program (PPM) activity has successfully increased Happy Tea's competitiveness as a local product while contributing to community-based economic empowerment.